Evaluating the Dynamics of State Da’wah Institution Relations in Indonesia: A Periodization Analysis of the Pre-Independence Era, Old Order, New Order, and Reform Era - Dida Novandika; Sa’idahtul Akmala Yusuf; Muhammad firdaus; Muhammad Yakub (Institut Agama Islam Negeri Pontianak, 2026)
This study aims to evaluate the dynamics of the relationship between the state and Islamic da’wah institutions in Indonesia through a periodization analysis covering the Pre-Independence era, the Old Order, the New Order, and the Reform era. The study is motivated by the importance of understanding how political regime changes and state policies have influenced the development, functions, and roles of da’wah institutions within Indonesia’s social, religious, and national life. Although previous studies have examined Islam state relations, political Islam, and civil society in Indonesia, limited attention has been given to the historical evolution of state da’wah institution relations across different political regimes. This study addresses this gap by offering a comprehensive periodization framework that captures the changing patterns of interaction between the state and da’wah institutions over time. This research employs a qualitative approach using the Systematic Literature Review (SLR) method by analysing various relevant academic sources related to the relationship between Islam and the state, Islamic organizations, civil society, and the development of da’wah institutions in Indonesia. The collected data were analysed using thematic analysis to identify patterns of interaction between the state and da’wah institutions across different historical periods. The findings reveal that the relationship between the state and da’wah institutions has shifted dynamically from a restrictive pattern during the Pre-Independence era, to a negotiative pattern during the Old Order, an accommodative-controlled pattern during the New Order, and a participatory pattern during the Reform era. The study also indicates that political policies constitute the primary factor influencing the development of da’wah institutions, while these institutions demonstrate a strong adaptive capacity in responding to political changes. The research contributes to enriching the discourse on state and civil society relations within the context of Indonesian Islam and offers a periodization framework for understanding the historical development of da’wah institutions comprehensively. The findings also provide practical implications for policymakers, Islamic organizations, and scholars in strengthening collaborative and democratic religious governance in Indonesia.